Antarctica – What role for the EU? - Dodds, Klaus; Raspotnik, Andreas (European Parliament, 2023)
Keywords: Antarktis; geopolitikk; politikk

The Antarctic Peninsula: Argentina and Chile in the era of global change - Vidal, Florian (The Polar Journal, 2023)
While Argentine-Chilean relations have long been swayed between cooperation and confrontation since their independence in the 19th century and a long-standing presence in Antarctica, the stretch between Tierra del Fuego to the Antarctic Peninsula stands as the closest lane (i.e. about 1,000 km) to any other continent. Despite their territorial dispute over islands on the fractured southern tip of South America and territorial claims on the Antarctic, their common diplo-matic ground successfully defuses any potential geopolitical instability. Along with Chile and Argentina, British claims overlap in the Antarctic Peninsula, which establishes unique geopolitical conditions in the whole of Antarctica. In this context, scientific missions and growing tourist activities could transform the region into the Antarctic gateway. From potential mineral resources exploitation to the United States- China global competition, the South Atlantic area could become a strategic bridgehead in light of the brewing geopolitical shift during the 21st century. Considering that climate change and geostrategic conditions evolve somewhat quickly to transform the Western Antarctic area, this article aims to assess and comprehend how these external drivers may affect the two South American countries. Given the fact that Antarctica is part of their respective national narrative, how do Argentina and Chile intend to maintain their presence and protect their interest in these shifting conditions? What are the vectors for partnering with the world’s great powers, such as China? Ultimately, could this space become a choke point through the 21st century?
Keywords: Antarktis; geopolitikk; politikk; ressurser